New Aspects of Zirconium Containing Organic Compounds - Marek, Ilan (Topics in Organometallic Chemistry, 2005)
Metal carbene complexes have made their way from organometallic curiosities to valuable reagents and catalysts. They offer novel synthetic opportunities in carbon-carbon bond formation based on either carbene-centered reactions or on metal-templated processes which makes them indispensable in modern synthetic methodology. The most prominent metal carbenes are now either commercially available or easy to synthesize and handle with modern laboratory techniques. This volume organized in eight chapters written by the leading scientists in the field illustrates the theoretical background, non-classical nucleophilic and cycloaddition patterns, chromium-templated benzannulation and photo-induced reactions, rhodium-catalyzed carbene transfer as well as the principles and applications of olefin metathesis which has coined the progress in synthetic methodology over the past decade. Designed for researchers in academia and industry as well as graduate students it presents the state-of-the-art potential of carbene complexes in modern organic synthesis.